2005
DOI: 10.4049/jimmunol.175.12.8280
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Induces Monocyte Chemotactic Protein-1 Production in Macrophages through the Phosphatidylinositol 3-Kinase/Akt and MEK/ERK1/2 Pathways

Abstract: Macrophages are activated during an inflammatory response and produce multiple inflammatory cytokines. IL-18 is one of the most important innate cytokines produced from macrophages in the early stages of the inflammatory immune response. Monocyte chemoattractant protein (MCP-1) is expressed in many inflammatory diseases such as multiple sclerosis and rheumatoid arthritis, and its expression is correlated with the severity of the disease. Both IL-18 and MCP-1 have been shown to be involved in inflammatory immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
74
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 46 publications
3
74
1
Order By: Relevance
“…We found a significant increase of p65 NF B nuclear localization in RA ST fibroblasts stimulated for 30 minutes with IL-18, compared with unstimulated cells (Figure 4C). In contrast to these results, some studies using mouse macrophages and epithelial cells did not demonstrate activation of NF B by IL-18 (40,46), again suggesting that such activation depends on the immune environment and cell type examined.…”
Section: Il-18 and Angiogenic Factorscontrasting
confidence: 61%
See 3 more Smart Citations
“…We found a significant increase of p65 NF B nuclear localization in RA ST fibroblasts stimulated for 30 minutes with IL-18, compared with unstimulated cells (Figure 4C). In contrast to these results, some studies using mouse macrophages and epithelial cells did not demonstrate activation of NF B by IL-18 (40,46), again suggesting that such activation depends on the immune environment and cell type examined.…”
Section: Il-18 and Angiogenic Factorscontrasting
confidence: 61%
“…Kanakaraj et al and Kalina et al found that IL-18 induces JNK and p38 MAPK activation in natural killer and T helper cell lines (42,43), in accordance with our findings in RA ST fibroblasts. In contrast to those reports, Yoo and colleagues did not observe activation of JNK and p38 MAPK in mouse macrophages (40), reaffirming that IL-18-induced activation of these signaling pathways may depend on cell type.…”
Section: Il-18 and Angiogenic Factorsmentioning
confidence: 77%
See 2 more Smart Citations
“…IL-18 is also a potent inducer of chemokines [i.e., monocyte chemoattractant protein-1 (MCP-1; CCL2), macrophage inflammatory protein-1␣ (CCL3), and IL-8] which recruit monocytes /macrophages and other leukocytes to sites of injury (56). We have previously demonstrated a pathological role for CCL2 (and CCL5) in adriamycin nephropathy (AN) (50), consistent with studies in other models of inflammatory kidney disease (35,38), and IL-18 has been shown to act as a chemoattractant of human CD4 ϩ T cells (24).…”
mentioning
confidence: 99%